Hyperledger frameworks with a special focus on Hyperledger Fabric - Krstić, Marija; Krstić, Lazar (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: The Blockchain market is a developing market, and many industries are increasingly aware of the importance of having and implementing Blockchain due to changing business conditions. After an introductory consideration of the Blockchain concept, the article focuses on the projects under the Linux Hyperledger Initiative, with particular reference to Hyperledger Fabric, notably on the concepts, architecture, organizational focus, private channels and smart contracts, as well as flow of transactions in the Hyperledger Fabric network. In the last, practical part of the paper, we presented a simulation of a business network and created a simple application for money exchange using the Hyperledger Fabric framework. The aim of the paper is to present the Hyperledger frameworks and highlight all the details of Hyperledger Fabric in order to determine whether its application in practice is justified.Methods: Basic methods (analysis, synthesis, deduction, induction, concretization, generalization) as well as general-scientific methods (analytical-deductive and comparative) were used.Results: All relevant features of Hyperledger Fabric were considered, a blockchain business network based on it was built, and an application for cash exchange through the network was created.Conclusion: Hyperledger Fabric is the most comprehensive and the most flexible Hyperledger framework with the largest number of use cases.
Keywords: Blockchain; Hyperledger; Hyperledger Fabric